The Effects of Stimulator, Waveform, and Current Direction on Intracortical Inhibition and Facilitation: A TMS Comparison Study - Wessel, Maximilian J.; Draaisma, Laurijn R.; Morishita, Takuya; Hummel, Friedhelm C. (Frontiers in Neuroscience, 2019)
Background: Cortical function is dependent on the balance between excitatory and inhibitory influences. In the human motor cortex, surrogates of these interactions can be measured in-vivo, non-invasively with double-pulse transcranial magnetic stimulation (TMS). To compare results from data acquired with different available setups and bring data together, it is inevitable to determine whether different TMS setups lead to comparable or differential results. Objective: We assessed and compared short intracortical inhibition (SICI) and intracortical facilitation (ICF) testing four different experimental conditions. Methods: SICI and ICF were studied with different stimulators (Magstim BiStim² or MagVenture MagPro X100), waveforms (monophasic or biphasic), current directions (anterior-posterior or posterior-anterior) at interstimulus intervals (ISIs) of 1, 3, 10, 15 ms. Results: We were not able to detect differences for SICI and ICF, when comparing the tested conditions, except for 3 ms SICI in which the anterior-posterior current direction led to stronger modulation. Correlation analysis suggested comparability for 3 ms SICI for the Magstim monophasic posterior-anterior condition with both tested MagVenture conditions. Conclusions: 3 ms SICI data sets obtained with two different, commonly used stimulators (Magstim BiStim² or MagVenture MagPro X100) with conventionally used stimulation parameters are largely comparable. This may allow the combination of data sets in an open science view.